Can touch this: training to correct police officer beliefs about overdose from incidental contact with fentanyl - Brandon del Pozo; Emily Sightes; Sunyou Kang; Jeremiah Goulka; Bradley Ray; Leo A. Beletsky (BMC, 2021)
Abstract Misinformation about overdose risk from accidentally inhaling or touching fentanyl is widespread among police in the United States. This may aggravate already elevated burdens of officer stress and burnout, while chilling lifesaving overdose response. Police education has shown promise in reducing false beliefs about fentanyl. To better understand the potential of training interventions in correcting officer knowledge, we administered a 10-min online training with corrective messaging about occupational overdose risk from fentanyl contact to 204 police officers in Indiana. Overall, 129 officers (63%) completed baseline survey and 69 (34%) completed follow-up instrument. Using a 6-point Likert scale, we documented assent with the statement: "First responders who encounter fentanyl are at great risk of overdose by touching it or inhaling it." At baseline, 79.8% expressed agreement, while 20.2% disagreed. At follow-up, 39.1% agreed, while 60.9% disagreed (p < .001). Baseline responses varied in that those officers without a college degree and those on patrol were more likely to report false beliefs. A brief online training intervention holds promise for correcting false beliefs about the risk of fentanyl overdose under circumstances commonly encountered by police.